2017
DOI: 10.18483/ijsci.1298
|View full text |Cite
|
Sign up to set email alerts
|

Ground Water and River Quality Assessment for Some Heavy Metals and Physicochemical Parameters in Wukari Town, Taraba State, Nigeria

Abstract: Abstract:With a few to assessing the qualities of water sources in Wukari local government area (LGA), a study was conducted on ground water and rivers in two settlements at Wukari LGA. For this purpose, some heavy metals (cadmium, lead, arsenic, iron, copper, mercury and manganese) and physicochemical parameters (temperature, turbidity, suspended solids, total dissolved solids, conductivity, pH, nitrate, phosphate, chloride, alkalinity, hardness and chemical/biochemical oxygen demand) were determined in water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…High concentrations of phosphate and nitrate nitrogen in a water sample are indicators of pollution and are largely responsible for eutrophic conditions (Aremu et al, 2017). Mean nitrate concentration in the Bantaji borehole water is higher than that in the Rafin-Kada borehole though the phosphate concentrations were found to be in the same range.…”
Section: Physicochemical Analysis Of Borehole Watermentioning
confidence: 99%
“…High concentrations of phosphate and nitrate nitrogen in a water sample are indicators of pollution and are largely responsible for eutrophic conditions (Aremu et al, 2017). Mean nitrate concentration in the Bantaji borehole water is higher than that in the Rafin-Kada borehole though the phosphate concentrations were found to be in the same range.…”
Section: Physicochemical Analysis Of Borehole Watermentioning
confidence: 99%
“…Lower concentrations of Hg and As could be due to reduced burning of fossils and petroleum pollution, which are the major sources of mercury in plants. A study by Aremu et al (2017) showed mercury and arsenic concentrations in groundwater in Wukari were low (0.0002 mg/kg and 0.003 mg/kg, respectively). The health implication of arsenic bioaccumulation includes lung and skin cancers due to free radicals attacking DNA and proteins (Hudson 2021).…”
Section: Discussionmentioning
confidence: 98%
“…The most commonly used pro-oxidants for degrading polyethylene presents heavy metals, such as cobalt (Co), manganese (Mn) and iron (Fe), in their composition. The concentration of heavy metals in the soil can have harmful effects on the environment and human health [20].On the other hand, organic pro-oxidants are an interesting alternative, once they have oxidative efficiency comparable to the heavy metal-based compounds and they are eco-friendly, as reported by others [21,22].…”
Section: Introductionmentioning
confidence: 94%